THE CORRELATION BETWEEN INTELLIGENCE QUOTIENT AND TRANSLATION COMPETENCE OF THE TENTH GRADE STUDENTS OF SMA N 3 PALEMBANG - Anggun Apriana; Akhyar Burhan; Hariswan Putra Jaya (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract: A study of the correlation between intelligence quotient and translation competence was carried out to the tenth grade students’ of SMA N 3 Palembang. The objectives of this study are to find out whether or not there is significant correlation between intelligent quotient and translation competence of tenth grade students’ of SMA N 3 Palembang, to find out whether or not there is significant correlation between intelligent quotient and translation competence of tenth grade students’ of SMA N 3 Palembang for high reading achievers, and to find out whether or not there is significant correlation between intelligent quotient and translation competence of tenth grade students’ of SMA N 3 Palembang for low reading achievers. The method used was correlation study. The population was the tenth grade students of SMA N 3 Palembang in an academic year 2011/2012 with the total number 256 students. The sample was 60 students that were taken by purposive sampling. The data were collected by using documentation and test. The data obtained was analyzed by using Pearson’s Product Moment Correlation Coefficient. The calculation was done by using SPSS (Statistical Package for Social Science) version 17.00. The result of the study showed that the correlation coefficient generally was 0.728; 0.669 for high reading achievers, and 0.723 for low reading achievers. It meant that there was positive and significant correlation between intelligent quotient and translation competence. Key words: correlation, intelligence quotient, translation competence